2015
DOI: 10.4236/ojped.2015.54043
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Respiratory Distress Syndrome among Preterm Infants Admitted to Neonatal Intensive Care Unit: A Retrospective Study

Abstract: Background: Respiratory distress syndrome (RDS) or hyaline membrane disease (HMD) is the most common cause of neonatal morbidity and mortality in preterm infants. We aimed to determine the frequency of RDS among 3 groups of preterm infants and the value of some related factors. Methods: A cross-sectional, descriptive analytical investigation was carried out in the NICU ward of Akbarabadi Hospital (Tehran-Iran) during spring 2011. Newborns' data were collected and assessed by using their hospital medical record… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 10 publications
3
18
2
Order By: Relevance
“…17 Shresta et al and karki et al, reported the most common condition leading to ICU admissions was respiratory distress. 14,18 In the present study majority of subjects had mild to moderate respiratory distress with only 4.7% had severe respiratory distress. For new born babies a review of following events in and around birth is important.…”
Section: Female Male Totalcontrasting
confidence: 40%
See 1 more Smart Citation
“…17 Shresta et al and karki et al, reported the most common condition leading to ICU admissions was respiratory distress. 14,18 In the present study majority of subjects had mild to moderate respiratory distress with only 4.7% had severe respiratory distress. For new born babies a review of following events in and around birth is important.…”
Section: Female Male Totalcontrasting
confidence: 40%
“…This study is similar to a study done in Iran which reported that 28-32 weeks of gestation accounted (52.1%) and 32-34 weeks for (30.1%). 14 In present study majority did not require intervention 49 (57.6%). Only Oxygen was needed in 8 (9.4%), bag and mask ventilation in 10(11.7%) and ventilation in 4(4.7%).…”
Section: Female Male Totalmentioning
confidence: 43%
“…Ramesh et al (2017) [11] studied the prevalence of antenatal steroids coverage in preterm labor and its influence on neonatal respiratory morbidity and mortality in kanyakumari district, India, they found that the incidence rates of RDS ranged from 86% at 24 weeks to less than 1% at 39 weeks, they mentioned that RDS should be anticipated in any preterm delivery, condition where amniotic fluid indices indicate pulmonary immaturity, and in any infant born to a diabetic mother. Saboute et al (2015) [12] concluded in their research that the incidence of respiratory distress syndrome among preterm infants admitted to neonatal intensive care unit as a retrospective study in Akbarabadi Hospital, Tehran, Iran, that RDS was frequent in preterm neonates with gestational age less than 32 weeks with incidence of 65.6% of all preterm infants. In Korwatia the incidence rate of RDS of preterm was accessed by kresimir et al (2017) [8] who studied the causes of respiratory distress among neonates of gestational age 32 weeks and more in Osijek hospital, during the year 2016, they found that 20% of admitted newborn in NICU have RD, 34% of preterm babies or older than 32 weeks, and 12% of term babies had RD.…”
Section: Discussionmentioning
confidence: 99%
“…RDS was the most common cause of neonatal morbidity in preterm neonate in other studies. 18 The order of these diseases as the common causes of admission varies from one study to another depending on the risk factors and the criteria used to diagnosis the diseases. 19 …”
Section: Discussionmentioning
confidence: 99%